Technology disrupting learners' and teachers' practices in Computer-Assisted Language Learning: an overview of the literature - Parmaxi, Antigoni; Zaphiris, Panayiotis (My University, 2015)
Abstract Amid the flurry of web, mobile and virtual technologies researchers and practitioners in the second language classroom strive to explore their affordances and challenges in the learning process. Yet, the efforts to explore the impact of technology remain disparate and unconnected unless we broaden our understanding on how teachers, policy makers and institutions support the use of such technologies. Attention is now focusing on what instructors and students know and what they need to acquaint with regard to technology – that is, the competences and understanding they need to develop if they are going to use technology efficiently and critically. In other words, the discussion now is about learners’ and instructors’ digital literacy. This study explores the research development with regard to learners’ variability and teacher training in the field of Computer-Assisted Language Learning (CALL). A systematic search of the published research was performed. Articles assessed for inclusion were published between January 2009 and September 2010 in four major journals devoted to CALL and had to meet subject-specific review criteria. The search provided a total of 163 articles of which 17 articles met the inclusion criteria. Moreover, articles published in the first quarter of 2013 were also included, in order to keep the review as up to date as possible. The review revealed the imperative to broaden our understanding of the new literacies that learners need to develop. These literacies relate to a specific language skill, to a specific technology or to the need to enhance self-directed techniques and strategies in order for learners to gain higher control over their learning. In this sense, researchers’ approach towards learners’ variability and the connected concept of digital literacy can be summarised in their effort to broaden learners’ strategies and deepen their autonomy. Research conducted with regard to teacher training focuses on how teachers can develop strategies, mechanisms and techniques for successfully dealing with teaching and managing online learning environments. Moreover, the emergence of new technologies raises the need for teachers to become aware not only of traditional paper-based teaching material but also to make effective use of the emerging technological tools, such as corpora, videoconferencing and webcamming. Still, identification and prioritization of key strategies and literacies that learners and instructors need to develop in order to achieve higher control in their learning lacks researchers’ attention. This study suggests that successful use of emerging technologies relies on maintaining relationship with learners and teachers, and continuing to give them the strategies and techniques that will allow them to confront with new instructional opportunities and challenges.
Keywords: Language learning; Digital literacy; Autonomy; Teacher training; E-learning